Integration of Wasathiyah Values in Community Service to Prevent Early Radicalism - Nashrul Mu'minin (Jurnal Pengabdian Bakti Akademisi, 2026)
The rise of early-stage radicalism among youth has become a critical challenge in contemporary society, particularly in the context of rapid digital transformation and the spread of extreme ideologies through social media. This study aims to analyze the integration of wasathiyah (moderation) values within community service programs as a strategic effort to prevent radical tendencies from an early age. Employing a qualitative approach based on Creswell’s research design, this study utilizes a literature review method by examining various scholarly sources, policy documents, and relevant reports related to Islamic education, community empowerment, and deradicalization efforts. The findings reveal that the incorporation of wasathiyah values—such as tolerance, balance, justice, and inclusivity—into community service activities significantly contributes to fostering critical thinking, strengthening social cohesion, and building resilience against radical narratives among participants. Furthermore, community-based programs that emphasize participatory engagement, contextual religious understanding, and collaborative learning between educators, religious leaders, and local communities are proven to be more effective in internalizing moderate Islamic values. The study also highlights that early prevention through educational and social interventions is more sustainable compared to reactive approaches. Therefore, integrating wasathiyah principles into structured community service initiatives not only enhances religious moderation but also supports the development of a peaceful and harmonious society. This research underscores the importance of multidimensional strategies in addressing radicalism and recommends the continuous development of inclusive and adaptive community service models grounded in Islamic moderation values.